Hospital costs of nosocomial multi-drug resistant Pseudomonas aeruginosa acquisition - Morales Eva; Cots Francesc; Sala Maria; Comas Mercè; Belvis Francesc; Riu Marta; Salvadó Margarita; Grau Santiago; Horcajada Juan P; Montero Maria; Castells Xavier (BMC, 2012)
Abstract Background We aimed to assess the hospital economic costs of nosocomial multi-drug resistant Pseudomonas aeruginosa acquisition. Methods A retrospective study of all hospital admissions between January 1, 2005, and December 31, 2006 was carried out in a 420-bed, urban, tertiary-care teaching hospital in Barcelona (Spain). All patients with a first positive clinical culture for P. aeruginosa more than 48 h after admission were included. Patient and hospitalization characteristics were collected from hospital and microbiology laboratory computerized records. According to antibiotic susceptibility, isolates were classified as non-resistant, resistant and multi-drug resistant. Cost estimation was based on a full-costing cost accounting system and on the criteria of clinical Activity-Based Costing methods. Multivariate analyses were performed using generalized linear models of log-transformed costs. Results Cost estimations were available for 402 nosocomial incident P. aeruginosa positive cultures. Their distribution by antibiotic susceptibility pattern was 37.1% non-resistant, 29.6% resistant and 33.3% multi-drug resistant. The total mean economic cost per admission of patients with multi-drug resistant P. aeruginosa strains was higher than that for non-resistant strains (15,265 vs. 4,933 Euros). In multivariate analysis, resistant and multi-drug resistant strains were independently predictive of an increased hospital total cost in compared with non-resistant strains (the incremental increase in total hospital cost was more than 1.37-fold and 1.77-fold that for non-resistant strains, respectively). Conclusions P. aeruginosa multi-drug resistance independently predicted higher hospital costs with a more than 70% increase per admission compared with non-resistant strains. Prevention of the nosocomial emergence and spread of antimicrobial resistant microorganisms is essential to limit the strong economic impact.